Correction to: TRIM50 suppressed hepatocarcinoma progression through directly targeting SNAIL for ubiquitous degradation. Issue 10 (October 2018) - Ma, Xiaoxiao; Ma, Xiaomin; Qiu, Yumin; Zhu, Lihui; Lin, Yueke; You, Yajing; Ma, Dapeng; Qin, Zhenzhi; Sun, Caiyu; Zhao, Yunxue; Sun, Yanlin; Han, Lihui
In Table 1, the number of patients with distant metastasis should be 13(16.5%), and the number of patients without distant metastasis should be 12(15.4%). The authors placed these two numbers inversely in the published paper.